Answer: The two factors are x+7 and x+2
The polynomial factors to (x+7)(x+2)
=========================================================
Step-by-step explanation:
In the upper left corner we have x^2. We get this by multiplying x with x
So,
x*x = x^2
This means you'll have x to the left of x^2, and another copy of x above the x^2. These new terms are outside the box.
Now ask yourself, what goes in the blank x times ___ = 7x. The answer must be "7" since x times 7 = 7x. So we'll write 7 above the 7x, outside the box. Up top, the x and 7 help form the factor (x+7)
Along the left side, the other factor is (x+2) for similar reasoning. Notice how we effectively have x times ___ = 2x and '2' must go in the blank. So a '2' must go to the left of the 2x.
Putting everything together, the two factors are (x+7) and (x+2).
Therefore, x^2+7x+2x+14 fully factors to (x+7)(x+2)
This is the same as saying x^2+9x+14 factors to (x+7)(x+2)
The order of multiplication doesn't matter.